Survive and thrive : - Quick, Tina L. (International Family Transitions, 2017)
This is the book that fills the information gap. From preparing to leave to understanding culture shock, beating homesickness, understanding American culture, dealing with academic challenges, staying healthy, managing money, choosing the right university and avoiding the pitfalls of independent living, "Survive and Thrive: The International Student’s Guide to Succeeding in the U.S." tackles the most common challenges international students face in their transition to the U.S. and gives them strategies for overcoming them. This is a guide book that helps these students understand what takes place in transition and gives them the tools and strategies they need to not only survive but to thrive in the adjustment. Parents will appreciate the chapter dedicated to how they can come alongside their students, prepare them for the journey and support them throughout this major transition as well as a chapter to help their student deal with re-entry.